Memorializing (violent) resistance to authoritarianism: challenges and tensions at Portugal’s Aljube Museum - resistance and freedom - Da Silva, R.; Dixit, P. (Critical Military Studies, 2024)
Museums play a critical role in constituting and communicating narratives about historical violence and connecting them to contemporary and future concerns. In this paper, we examine the memorialization of resistance movements, especially resistance to authoritarianism and state violence, as exemplified at the Aljube Museum – Resistance and Freedom in Lisbon, Portugal. We offer a methodological and theoretical discussion on storytelling and autoethnography in understanding the narratives of historical violence and war, focusing on representations of historical resistance movements and their uses of violence. We argue that the museum has avoided grappling with armed resistance as a method of effecting change and challenging authoritarianism by crafting a coherent and unitary narrative about oppression and non-violent resistance that downplays violent opposition to authoritarianism. After outlining some silences noted in the museum’s representations of resistance, we offer a counter-memory that discusses the role of non-state armed actors and shows multiple ways in which historical authoritarianism has been resisted and fought.